Tailoring BaCe0.8Y0.2O3 proton-conducting oxide with U ions for an enhanced stability. Issue 12 (15th June 2022) - Yu, Shoufu; Wang, Yu; Bi, Lei
Abstract: Uranium cations were immobilized in the proton-conducting oxide BaCe0.8 Y0.2 O3 (BCY) by partially replacing Ce with U. Uranium cations can be incorporated into the BCY lattice to form the new BaCe0.7 Y0.2 U0.1 O3 (BCUY) compound. This new BCUY material shows an improved chemical stability against CO2 compared with the traditional BCY material. The first-principles calculations reveal that the doping of U elevates the energy barrier for the interaction between BCUY and CO2, which is the reason for the improved chemical stability. Despite the improved chemical stability, U-doping inhibits the grain growth for the BaCeO3 proton-conducting oxide, making the grain size of the sintered BCUY reach only 0.5 μm, which is approximately one-tenth of that for BCY sintered at the same temperature. As a result, the conductivity of BCUY is 2.8 × 10 −3 S cm −1 at 700 °C. The H-SOFC using a BCUY electrolyte reaches a peak power density of 237 mW cm −2 at 700 °C, which is lower than that for BCY cells, but comparable to that using other proton-conducting electrolytes. The current study demonstrates that U cations can be immobilized in BCY proton-conducting oxide, and that U-doping improves the stability of the material at the cost of reducing the sinterability, and thus conductivity.